Evolution des glaciers et du pergélisol depuis le dernier maximum glaciaire dans la région du mont Gelé-Mont Fort (Alpes Valaisannes, Suisse) : chronologie, modalités de la dernière déglaciation et datations des âges d’exposition à l’aide du marteau de Schmidt - Scapozza, Cristian (Quaternaire, 2017)
Knowledge about the morphoclimatic evolution of the Alps during the Lateglacial and the Holocene considerably evolved during the last century in particular in the eastern part of the Alps, even if little interest was accorded to the periglacial zone. This latter being located above the upper limit of the forest, it is very difficult to find organic remains for absolute time calibrations. Subject of many studies during the seventies and the eighties, the Valais Alps have lost in interest in studies concerning the deglaciation, probably because of the difficulties in defining a complete deglaciation sequence encompassing the entire Lateglacial and of the limited number of available numerical dates. In the first part, the evolution of glaciers and rock glaciers in five glacial basins of the Mont Gelé-Mont Fort region since the end of the last glaciation was reconstructed on the basis of a palaeoenvironmental approach. The reconstruction of the glacier’s equilibrium line altitude depression and of the permafrost depression allowed 16 local stadials, regrouped in five regional glacial stadials and three generations of rock glaciers, to be defined. Palaeotemperatures and palaeoprecipitations calculated at the equilibrium line altitude and at the lower limit of permafrost allowed a palaeoclimatic chronology, on which the glacial and periglacial history of the region was correlated, to be composed. Thereafter, this chronology was refined thanks to Schmidt hammer exposure-age dating. Twelve rock glaciers, two protalus ramparts, three talus slopes, thirteen morainic ridges and three roches moutonnées have been dated applying this method. The measured R-values (adimensional) are comprised between 43 on a morainic ridge of the end of the Oldest Dryas and 59 on a morainic ridge of 1861 AD. Thanks to the relative dating of glacial landforms with the palaeogeographic method, it was possible to use the R-values measured on surfaces of known age to calibrate the exposure-ages of the studied landforms. According to the dating ...